Atmospheric-pressure dielectric barrier discharge with capillary injection for gas-phase nanoparticle synthesis. (22nd July 2015) - Ghosh, Souvik; Liu, Tianqi; Bilici, Mihai; Cole, Jonathan; Huang, I-Min; Staack, David; Mariotti, Davide; Sankaran, R Mohan
Abstract: We present an atmospheric-pressure dielectric barrier discharge (DBD) reactor for gas-phase nanoparticle synthesis. Nickel nanoparticles are synthesized by homogenous nucleation from nickelocene vapor and characterized online by aerosol mobility measurements. The effects of residence time and precursor concentration on particle growth are studied. We find that narrower distributions of smaller particles are produced by decreasing the precursor concentration, in agreement with vapor nucleation theory, but larger particles and aggregates form at higher gas flow rates where the mean residence time should be reduced, suggesting a cooling effect that leads to enhanced particle nucleation. In comparison, incorporating a capillary gas injector to alter the velocity profile is found to significantly reduce particle size and agglomeration. These results suggest that capillary gas injection is a better approach to decreasing the mean residence time and narrowing the residence time distribution for nanoparticle growth by producing a sharp and narrow velocity profile.